Exploring time-killing and biofilm inhibition potential of bioactive proteins extracted from two varieties of Pleurotus ostreatus - Gangwar, Reena; Salem, Mohamed M.; Maurya, Vineet Kumar; Bekhit, Mounir M.; Singh, Nisha; Amara, Amro Abd Al Fattah; Sahu, Ram Kumar; Ibrahim, Mohamed A. (Frontiers in Microbiology, 2024)
The study aimed to compare the antimicrobial potential of Bioactive Proteins (BAPs) extracted from Pleurotus ostreatus cultivated (PoC) and Pleurotus ostreatus wild (PoW) mushrooms against oral cavity pathogens causing dental caries. The antibiofilm and antioxidant properties of these BAPs were also examined. BAPs were extracted from both PoC and PoW using a TCA-acetone method. Antimicrobial activities were tested against seven bacteria and one fungus using agar well diffusion and MIC determination. Antibiofilm activity was assessed via MTTIn response to the comment by reviewer-1, the word 'bioactive peptides' has been changed to 'bioactive proteins', because protein extraction is a simple procedure and doesn't requires sophisticated instruments (HPLC, Size exclusion chromatography, Reverse phase chromatography), which are required for peptide extraction. Moreover, the study is also based on extracted bioactive proteins (BAPs). Hence in further sections of manuscript, the word 'bioactive peptide' has been chaned to 'bioactive proteins' assay, while DPPH and erythrocyte lysis tests evaluated free radical scavenging potential. PoC exhibited superior antimicrobial activity with lower MIC and MBC values, indicating higher efficacy against pathogens. The time-kill assay demonstrated significant reduction in viable bacilli count, disrupting biofilm integrity at increasing BAPs concentrations. While PoW showed better DPPH scavenging, PoC had slightly lower free radical scavenging activity. In conclusion, both PoC and PoW BAPs effectively inhibited microbial growth, with PoC demonstrating higher inhibition potential against dental caries pathogens. PoW displayed stronger antioxidant activity, while antibiofilm potential of both was comparable. These findings propose the use of both PoC and PoW BAPs in dental caries treatments to combat diverse oral microbial pathogens.